The Influence of Sorting of Hatching Eggs on the Indicators of Growing of Broiler Chickens - Vecheria, Julia; Prokopenko, Nataliia (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2020)
The high homogeneity of the chicken-broilers population is important during the whole period of growth, starting from the daytime age. Completing the herd with chickens, the body masses of which are homogeneous allows achieving high industrial indicators. That‘s why, the estimation of the indicators of chicken-broilers growing, obtained during the incubation of eggs (mass more than 70 g) with an additional division into groups by mass, is actual. The materials for the experiment were incubated eggs of hens of the parent flock of the cross “Cobb-500“ and the one-day-old chicken-broilers. Hatching eggs before incubation were divided into 4 groups: I – control (uncalibrated hatching eggs), II – 70–79 g, III – 70–74 and IV – 75–79 g. The distribution of hatching eggs by mass allowing greatly improve the results growing of broiler chickens – observed an increase in alive mass on 1.61… 5.59%, uniformity of poultry on 4.19… 9.57% and viability on 5.42… 5.84%.